A case study of a simultaneous integration in an SME: Implementation process and cost analysis. Issue 2 (5th February 2018) - Llonch, Marc; Bernardo, Merce; Presas, Pilar
Abstract : Purpose: The purpose of this paper is to analyze the simultaneous implementation of an integrated management system (IMS) in a small and medium-sized enterprise (SME) and its impact on costs. Design/methodology/approach: Based on a case study, the paper presents and analyzes the implementation of the ISO 9001 and ISO 14001 management system (MS) standards. The organization analyzed is an SME of the heating and air conditioning sector that had no MSs implemented (common in the sector) and decided to implement an IMS based on both function-specific MS standards (MSSs) and also achieving the separated certification. The analysis of expected and real costs is also presented. Findings: The results show that a simultaneous integration is possible and the cost analysis evidences the improvement of the organization's efficiency. The certificates for both MSSs were also achieved. These findings help in confirming theoretical statement posed in the literature of the integration of MSs: integration strategy, methodology and level. The organization values this integrated implementation as very positive internally and externally, as this is one of the first organizations of the sector implementing and integrating the ISO 9001 and ISO 14001. Originality/value: Although studies analyzing empirically the integration of MSs have been widely published in recent years, to the best of the authors' knowledge, this is one of the first papers analyzing the implementation of an IMS directly and analyzing its costs. In addition, this paper provides evidence that those organizations implementing integration later than others, can learn from the beginners' experience.